Uso de inteligencia artificial en la personalización del aprendizaje: un enfoque para la gestión eficiente del aprendizaje en ciencias naturales. - Carrillo Uvidia, Jorge Luis (2024)
The research work, "Use of Artificial Intelligence in the Personalization of Learning: An Approach for the Efficient Management of Learning in Natural Sciences," addresses a comprehensive perspective on using artificial intelligence (AI) in personalizing learning. This research aims to develop a massive open online course (MOOC) designed through the Institutional Management System for Open Education (SIGEA) of the UNACH. The project seeks to train students to take advantage of AI within their teaching methodologies, facing the challenges of an educational environment moving towards digitalization. It adopted a mixed approach and employed a quasi-experimental design that combined diagnostic, descriptive, exploratory, bibliographic, and field analysis. As part of the methodology, the researcher conducted surveys and interviews to collect information from 26 fifth-semester students of the Pedagogy in Experimental Sciences, emphasizing Chemistry and Biology. The findings show that incorporating AI in education improves the personalization of learning and facilitates more effective educational management. Likewise, it was possible to identify that free AI-based tools allow personalizing learning experiences according to the needs of each student, promoting more meaningful and effective processes. In conclusion, incorporating AI in education positively impacts personalized learning and boosts educators' pedagogical and technological development, promoting innovative and effective teaching practices.